IMPLIKASI HUKUM UNDANG-UNDANG NOMOR 06 TAHUN 2023 PADA SISTEM PENDAFTARAN MEREK DI INDONESIA - Dina Fitria; Elfrida Ratnawati Gultom (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Pros and cons are present among legal experts along with the passage of Law No. 11 of 2020 concerning Job Creation. This happened because this regulation was deemed problematic in its formulation, both formally and substantially. One interesting thing that happened after the enactment of Law no. 11 of 2020 concerning Job Creation is a substantial transition to the provisions of Law no. 20 of 2016 concerning Trademarks and Geographical Indications, and this has an impact on the trademark registration system in Indonesia. To examine this, research was carried out on two issues, which consisted of: